Nutritional Indices And Biochemical Constituents In The Prawn Macrobrachium Malcolmsonii Fed With Formulated Feeds - P. SARAVANA BHAVAN; S. RADHAKRISHNAN (International Journal of Pharma and Bio Sciences, 2012)
This study was conducted to assess and categorize the feeds formulated with three different combinations of cereals and pulses (black gram and maize; Bengal gram and barley; red gram and rice) along with coconut oilcake and soya meal for sustainable maintenance of Macrobrachium malcolmsonii post larvae (PL). Two types of feeds in each combination (type-A: 25% pulse + 25% cereal; type-B: 40% pulse + 10% cereal) were prepared along with equal proportion of coconut oilcake and soya meal (20% each). Tapioca flour (5%) and egg albumin (4%) were used as binding agents. 1% of vitamin B-complex with vitamin-C was also mixed. These feeds were fed to M. malcolmsonii PL for a period of 45 days. Commercially available standard Scampi feed was served as control. The overall influence of these feeds on survival, growth and concentrations of total protein, amino acid, carbohydrate and lipid of PL were found to be significantly higher (P<0.225) in scampi feed followed by the feeds rich in pulse (type-B) and the feeds with equal proportion of pulse and cereal (type-A). Among three combinations of pulses and cereals the feed formulated with black gram and maize showed the best overall performance, followed by Bengal gram and barley, and red gram and rice. Therefore, on-farm feed formulation can be made with these commodities of pulses and cereals for sustainable culture of Macrobrachium.